Searching for the Musical Tradition of the Colombian Caribbean. Case Study of Petrona Martínez, the Queen of Bullerengue - Salazar P., Jaime A. (2023)
In 1998, the French traditional music record label Ocora Radio France released the album Colombie • Le bullerengue/Petrona Martínez, a recording that opened the doors to national and international success for Petrona Martínez and granted the bullerengue with worldwide diffusion. Through the biographical analysis of the cantadora as well as the negotiation and recording process of this album, this article aims to expose some of the diffusion mechanisms of tradition that influence the construction and stabilization of cultural and ethnic categories in the context of Afro-Colombian musical practices.